CONNAISSANCE DU PALUDISME CHEZ LES FEMMES ENCEINTES DE LA ZONE DE SANTE D’ALUNGULI/KINDU - RASHIDI KITOKO NORBERT , KILEWA; KETIBUNA, KIFINGA; MUPEPE ROMAIN, TSIKININGI; MATONDO, KAFINGA; LUZOLO EMERY, KAFINGA; MILONDO ALPHONSE , MASANDI (International Journal For Research In Health Sciences And Nursing, 2023)
Malaria is on of the most serious health problems despite the existence of preventive and curatuive measures. Nearly 40% of the world’s population is exposed to this parasitosis. This research is carried out through a cross-descriptive approach correlating it. We used the survey method, supported by the interview technique guided by a simple questionnaire. To analyze our data, we used calculations of the arithmetic mean ; stadard deviation, coefficient of variation, Student t test, Snedecor’s F ratio and multivariate regression. The summary of the results is as follows : Overall, knowlodge of malaria among pregnant women in the health zone of Alunguli is insufficient. The yield reflecting this knowledge is less than 50%. This invalidated the first hypothesis. The variable age, parity, level of education, marittal status and health area of residence of the subjects did not influence knowledge of malaria. Therefore, are not determinants of it. This invalidated the second hypothesis.